1982
DOI: 10.1161/01.cir.66.4.732
|View full text |Cite
|
Sign up to set email alerts
|

Precordial ST-segment depression during acute inferior myocardial infarction: clinical, scintigraphic and angiographic correlations.

Abstract: SUMMARY The cause and associated pathophysiology of precordial ST-segment depression (ST {) during acute inferior myocardial infarction (IMI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(28 citation statements)
references
References 30 publications
2
24
2
Order By: Relevance
“…However, no statistical significant mean age difference was found between two groups of patients (p>0.05). Similarly, another study 9 showed the mean age was found 50±8 years in group I and 53±5 years in group II, which is closely resembled with the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, no statistical significant mean age difference was found between two groups of patients (p>0.05). Similarly, another study 9 showed the mean age was found 50±8 years in group I and 53±5 years in group II, which is closely resembled with the current study.…”
Section: Discussionsupporting
confidence: 91%
“…9 In general, the 12-lead ECG is less sensitive in identifying left circumflex occlusion. Huey, et al, 1988 found that 52% of patients with acute MI from left circumflex disease did not show any ST segment elevation, while other investigators reported that acute left circumflex occlusion either does not bring about any changes at all in the standard 12-lead ECG 16 or generates only ST depression in the precordial leads (Jacobs, et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] As part of a study looking at partial-thickness ischemia in an experimental animal model, 9 we observed that ST depression accompanied some episodes of full-thickness ischemia and not others. The literature reflecting experimental infarction has shown that full-thickness ischemia was associated with a region of epicardial ST elevation over the ischemia with minimal changes elsewhere.…”
mentioning
confidence: 79%
“…For each patient autologous leucocytes labelled with "'In were prepared using "'In-hydroxyquinoline (oxine) solution (Amersham International IN 15P), the labelling dose being in the range [10][11][12][13][14][15][16][17][18][19][20] MBq (270-540 1iCi). A mean labelling efficiency of 78.50% (range 62-95") was achieved for all patients studied.…”
Section: Methodsmentioning
confidence: 99%
“…To examine this possibility 103 consecutive patients who underwent exercise testing early after myocardial infarction were reviewed. Treadmill exercise testing was performed a mean of 12 (range 5-30) days after infarction using a limited Naughton protocol. Resting electrocardiograms were independently reviewed by two observers (KJ and DSR), and equivocal ST changes were referred 635 to a third party for arbitration (DGJ).…”
Section: Jennings Douglas S Reid Desmond G Julian Abstractmentioning
confidence: 99%